2013
DOI: 10.1186/1471-230x-13-98
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microdialysis reflects the neuroprotective effect of fractionated plasma separation and adsorption in acute liver failure better and earlier than intracranial pressure: a controlled study in pigs

Abstract: BackgroundCerebral edema is a well-recognized and potentially fatal complication of acute liver failure (ALF). The effectiveness of treatments that address intracranial hypertension is generally assessed by measuring intracranial pressure (ICP). The aim of this study was to determine the role of cerebral microdialysis in monitoring the efficacy of fractionated plasma separation and adsorption (FPSA) treatment for ALF. We hypothesized that in ALF cerebral microdialysis reflects the benefits of FPSA treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Increased brain tissue or extracellular lactate content (or lactate/pyruvate ratio) is has been recorded, and considered to reflect impaired oxidative metabolism, in brain of comatose human ALF patients (Bjerring et al, 2010; Tofteng et al, 2002), of rats (Zwingmann et al, 2003) or guinea pigs in which ALF was induced by hepatic artery ligation (HAL) (Rose et al, 2007), and in pigs with surgically resected liver (Prazak et al, 2013). Here we found that extracellular lactate does not change in the brains of mice under conditions where ALF was induced by a hepatotoxin, AOM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased brain tissue or extracellular lactate content (or lactate/pyruvate ratio) is has been recorded, and considered to reflect impaired oxidative metabolism, in brain of comatose human ALF patients (Bjerring et al, 2010; Tofteng et al, 2002), of rats (Zwingmann et al, 2003) or guinea pigs in which ALF was induced by hepatic artery ligation (HAL) (Rose et al, 2007), and in pigs with surgically resected liver (Prazak et al, 2013). Here we found that extracellular lactate does not change in the brains of mice under conditions where ALF was induced by a hepatotoxin, AOM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with hepatotoxic drug models, surgical models are preferred increasingly by some researchers, particularly in large animals [24, 25]. Generally, the primary surgical procedures used for modeling could be classified into three major categories: devascularization (total and partial), hepatectomy (total and partial), and a combination of both [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses (Kjaergard et al 2003, Struecker et al 2014) have reported no beneficial effects of application of artificial and bioartificial liver support systems on the mortality of patients with ALF. It was shown that while such support devices are safe for acute application and can improve biochemical markers (Prazak et al 2013, Ryska et al 2009, Struecker et al 2014, Stutchfield et al 2011), they do not generally improve survival rate of patients with ALF (Pless 2010, Struecker et al 2014, Stutchfield et al 2011 and, remarkably, no bioartificial liver support system has obtained approval from U.S. Food and Drug Administration for standard clinical uses (Arenas-Herrera et al 2013). It will be noted that the original notion that the critical "failed" function in ALF is detoxification, and thus approaches ensuring this are adequate for treatment of ALF, proved inaccurate (Banares et al 2013, Selden andHodgson 2004).…”
Section: Discussionmentioning
confidence: 99%